Genotype‐phenotype correlation in a novel ABHD12 mutation underlying PHARC syndrome. Issue 2 (24th February 2020) - Thimm, Andreas; Rahal, Ahmad; Schoen, Ulrike; Abicht, Angela; Klebe, Stephan; Kleinschnitz, Christoph; Hagenacker, Tim; Stettner, Mark
Abstract: PHARC syndrome is a rare neurodegenerative disorder caused by mutations in the ABHD12 gene. It is a genetically heterogeneous and clinically variable disease, which is characterized by demyelinating polyneuropathy, hearing loss, cerebellar ataxia, retinitis pigmentosa, and early‐onset cataract and can easily be misdiagnosed as other neurologic disorders with a similar clinical picture, such as Charcot‐Marie‐Tooth disease and Refsum disease. We describe the genotype‐phenotype correlation of two siblings with a novel genotype underlying PHARC syndrome. The genotype was identified using next‐generation sequencing. We examined both patients by means of thorough history taking and clinical examination, nerve conduction studies (NCS), brain imaging, and optical coherence tomography to establish a genotype‐phenotype correlation. We identified a novel homozygous point mutation (c.784C > T, p.Arg262*) in the ABHD12 gene. This mutation was detected in both siblings, who had bilateral hearing loss and cataracts, signs of cerebellar ataxia, and neuropathy with a primarily demyelinating pattern in NCS. In one case, retinitis pigmentosa was also evident. As PHARC syndrome is a rare autosomal recessive disorder, our findings highlight the importance of an interdisciplinary diagnostic workup with clinical and molecular genetic testing to avoid a misdiagnosis as Charcot‐Marie‐Tooth disease or Refsum disease.